TINJAUAN ATAS PROSES VERIFIKASI DAN POS-POS ATAS LAPORAN REALISASI ANGGARAN SEMESTER I 2019 BADAN PENYULUHAN DAN PENGEMBANGAN SDM PERTANIAN KEMENTERIAN PERTANIAN REPUBLIK INDONESIA - Zaqih Wildan Firdaus (2020)
The Field Work Practice (PKL) activity aims to apply the knowledge that has been obtained from semester 1 until semester 5 and to increase the knowledge and science obtained in the agency where the street vendor is. Fieldwork practices are conducted for 3 month starting December 16 until march 13 2020 at the Agricultural Human Resources Development and Counseling Agency (BPPSDMP) of the Indonesian Ministry of Agriculture. In carrying out practical activities, it is positioned in the Accounting and Verification Subdivision to help verify and prepare financial statements. Constraints faced in the Field Work Practice are still lack of experience regarding the verification process of various supporting source documents, the flow of the verification process, making a verification note, and the process of preparing the Financial Statements. The compiled Financial Statements are 2019 Semester 1 Financial Statements in the form of Budget Realization Reports, Balance Sheet, Operational Reports, Equity Change Reports, and Notes to Financial Statements (CaLK) and referring to Government Regulation Number 71 of 2010 concerning Government Accounting Standards and financial management principles healthy in government. The Budget Realization Report discussed was in the form of the realization of income and expenditure reports during the semester 1 of 2019.